Investment resources of the mining and metallurgical complex: management features, analysis of the composition, structure and sources of their formation - E. N. Gavrilova (Вестник университета)
In the conditions of the modern economy, an especially important area of economic activity of any company is its investment activity, which is associated with the investment of certain funds in the implementation of both long-term and medium-term projects. Without increasing in the receipt of financial resources from various sources used for investment, it is impossible to achieve the largescale goals of innovative, technological and information development of the socio-economic sphere in Russia. The purpose of this article is to study the specifics of the management of investment resources of metallurgical and mining companies in the country, as well as the analysis of the composition, structure of their investment resources and sources of their formation. The methods of comparative analysis, a systematic approach to the study of information, graphical methods are used. This article considers the factors affecting the efficiency of investment activities of mining and metallurgical enterprises. The measures for the implementation of the strategy of sustainable development are proposed. The features of the formation of the composition and structure of investment resources of companies in the industry are revealed.